PENGARUH VARIASI SUDUT PENGELASAN KAMPUH V DAN KETINGGIAN ELEKTRIKAL STICK OUT PENGELASAN GMAW TERHADAP SIFAT MEKANIS BAJA ST-42 - Fredrik Demataco; Nevada. J.M Nanulaita; Lukman Hadiwijaya; Ratna Ayu Pawestri Kusuma Dewi (Journal Mechanical Engineering, 2023)
GMAW (Gas Metal Arc Welding), which is a solid or tubular welding electrode that is fed continuously mechanically from a roll of electrode wire inside the welding machine. The electrode is fed via a gun or torch by maintaining the height of the arc formed between the tip of the electrode wire and the material being welded or the base metal. GMAW (Gas Metal Arc Welding) is MAG (Metal Active Gas) and MIG (Metal Inert Gas) welding which is very efficient and fast in the process.Low carbon steel contains less than 0.3% carbon in the carbon steel mixture. Low carbon steel cannot be hardened because the carbon content is not enough to form a martensite structure. Welded joints are material or plate joints that are used for the welding process with the aim of getting maximum penetration from the joint.In this research, we are looking at the effect of the GMAW (Gas Metal Arc Welding) welding process with MIG (Metal Inert Gas) type on ST-42 steel by varying the V seam angle with a stick out height of 5 mm on the mechanical properties in the HAZ area.The hardness value before the welding process at an angle of 15 is in the HAZ area of 30.03 HRD for corners 30 and 45 is 32.51 HRD and 33.98 HRD, while for the impact strength at an angle of 15 is 0.2725 J/mm2, an angle of 30  and 45 namely 0.2439 J/mm2 and 0.2320 J/mm2 Keywords: Welding, HAZ (Heat Affected Zone), Impact Strength, Hardness